Effect of Postpartum Pelvic Floor Muscles Training in Pelvic Floor Muscles Strength on Postpartum Women with Stress Urinary Incontinence - Jerisatrio S Tarukallo; David Lotisna; Nugraha U Pelupessy (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To evaluate the effect of pelvic floor training (Kegelexercise) on pelvic floor muscle strength in postpartum womenwith SUI.Methods: Thirty-five birth vaginally postpartum women with SUIwere experimentally enrolled. After four weeks of postpartumobservation, the diagnosis of SUI confirmed, and all of these womenwere asked to complete the International Consultation onIncontinence Questionnaire-Sort Form (ICIQ-SF) questionnaire.The strength of the pelvic floor muscle measured with perineometerevery once in 3 weeks for 12 weeks of Kegel exercise. SUI severityassessed with ICIQ-SF after completing the Kegel exercise. A pairedt-test was used to compare measurement results between ICIQ-SFquestionnaire and perineometer and multiple linear regressionmodels was used for multivariate analysis. A p value of less than 0.05was taken to be statistically significant.Results: Findings show a significant difference between clinicalvariables (parity, neonates birth weight, perineal tear grade, BMI)and the improvement of pelvic floor muscles before and afterperformed the Kegel exercise (all p<0.05). The pelvic floormuscles strength significantly improved (p=0.000) after Kegelexercise both in ICIQ-SF questionnaire and perineometermeasurement.Conclusion: Pelvic muscles floor training or Kegel exercise improvepelvic muscles floor strength in postpartum women with SUI.[Indones J Obstet Gynecol 2018; 6-2: 114-118]Keywords: pelvic muscles floor training, postpartum, stress urinaryincontinence